Comparison of complete multi-level vs. iliac-only revascularization for concomitant iliac and superficial femoral artery occlusive disease - Ren, Hong Cheng; Li, Tian Run; Zhuang, Jin Man; Li, Xuan; Luan, Jing Yuan; Wang, Chang Ming; Ding, Ming Chao (Frontiers in Surgery, 2023)
Objective The aim of this study is to compare the efficacy and safety of complete multi-level vs. iliac-only revascularization for the treatment of concomitant iliac and superficial femoral artery (SFA) occlusive disease. Methods A total of 139 consecutive adult patients with severe stenosis and occlusive iliac and SFA disease with Rutherford categories 2–5 underwent multi-level (n = 71) and iliac-only (n = 68) revascularization at the Department of Intervention Vascular Surgery, Peking University Third Hospital, and Aerospace Center Hospital, between March 2015 and June 2017. Improvement in Rutherford class, perioperative major adverse events, the length of stay, survival rate, and limb salvage rate were assessed. The neutrophil–lymphocyte ratio and platelet–lymphocyte ratio were compared between the two groups. Results At 48 months, improvement in the Rutherford category was observed in the two groups with no significant difference (P = 0.809). Additionally, the two groups were similar concerning the primary patency (84.0% vs. 79.1%, P = 0.717) and limb salvage rate (93.1% vs. 91.3%, P = 0.781). A higher proportion of the perioperative major adverse events (33.8% vs. 27.9%, P = 0.455), the all-cause mortality (11.3% vs. 8.8%, P = 0.632), and the average length of hospital stay [7.0 (6.0, 11.0) vs. 7.0 (5.0, 8.0), P = 0.037] were seen in the multi-level group compared with the iliac-only group. Conclusion For concomitant iliac and superficial femoral artery occlusive disease, iliac-only revascularization has favorable efficacy and safety outcomes compared with complete multi-level revascularization in selected patients with patent profunda femoris artery and at least one healthy outflow tract of the infrapopliteal artery.